91 Intra-Cardiac Echocardiography (ICE) to Guide Alcohol Septal Ablation (ASA) in Hypertrophic Obstructive Cardiomyopathy (HOCM): A Prospective Comparison Study against Trans-Thoracic Echocardiography (TTE). (6th June 2015) - Cooper, Robert; Shahzad, Adeel; Newton, James; Vejlstrup, Niels; Sharma, Vishal; Axelsson, Anna; Ormerod, Oliver; Stables, Rodney
Abstract : Introduction: Successful alcohol septal ablation (ASA) in hypertrophic obstructive cardiomyopathy (HOCM) reduces LVOT gradients. A third of patients do not respond; inaccurate location of the iatrogenic infarct can be responsible. Myocardial contrast studies following injection into a septal coronary artery guide ASA. Transthoracic echocardiography (TTE) is the current gold standard. TTE can be difficult in the lab environment. The ideal echocardiographic modality will see crucial anatomy relevant to ASA and delineate myocardial contrast well. We assessed ICE against TTE in ASA. Methods: The ability of ICE and TTE to see relevant anatomy was assessed in two phases. Phase one recruited 25 successive patients undergoing PFO closure under ICE guidance. This was predominantly a feasibility study. Phase 2 recruited 20 successive HOCM patients undergoing ASA. The ability to assess myocardial contrast was assessed in phase 2. A scoring system to assess three key domains was used (see Table 1). Two independent experts scored paired, off-line TTE and ICE images, a score was allocated to each modality in each domain. Results: Phase 1: ICE catheter manipulation to visualise the relevant anatomy was quick and safe. TTE was superior in viewing MV anatomy and SAM (score 1.4 vs. 0.4, p < 0.0001) but ICE visualised the target septum better (1.66 vs 1.08; p < 0.0001). There was no difference in ability to see adjacent structures. Phase 2: ICE was superior in viewing MV anatomy (1.88 vs 1.6; p = 0.02), superior catheter manipulation caused better scores in ICE. There was no difference in assessing target septum. TTE was superior in assessing adjacent structures (1.03 vs 0.63, p = 0.002). Myocardial Contrast injection was performed in 19/20 patients: ICE was able to visualise contrast satisfactorily in just 2/19. This was due to dense acoustic shadowing with inability to comment on surrounding myocardium (8/19), and inadequate opacification of the myocardium (6/19). Contrast localised to myocardium outside the field in 3/19 (RV cavity). This was not seen on ICE due to a narrower field of echo. TTE saw myocardial contrast location in all. Conclusions: ICE cannot be used to guide ASA due to the inability to describe myocardial contrast distribution. ICE was better at seeing the motion of the MV, but TTE saw adjacent structures better. The ability of ICE to see SAM of the MV may lend itself to non-surgical septal reduction therapies that are not reliant on myocardial contrast.